Real Burials or Cenotaphs? A Study of the Mysterious Under-mound Funerary Constructions of the Trzciniec Cultural Circle - Romaniszyn, J.; Makarowicz, P. (Археологія і давня історія України, 2021)
This article presents a recently recognized type of Trzciniec Cultural Circe (TCC) funerary structure, which over the last decade has been excavated in the cemeteries of Bukivna, Nieciecz Włościańska, and has also been identified during the study of archival material from Komariv. These constructions are characterized by the placement of stones in the corners and along the sides of a rectangular plan. Due to the lack of skeletal remains, these structures are sometimes interpreted as symbolic graves (cenotaphs). Based on multidisciplinary methods, including radiocarbon, geochemical and geological analyzes, excavation, as well as study of archival documentation, the authors can state these features occurred in different enclaves of the TCC and were an important component of the funeral rite during the classical stage of the development of this cultural formation. Their form, structure, location, and inventory also indicate that these unique features probably played an important and universal role in the varied and multidimensional TCC funeral ceremonies.